2013
DOI: 10.1177/0956462413490677
|View full text |Cite
|
Sign up to set email alerts
|

High syphilis but low HIV prevalence rates among pregnant women in New Caledonia

Abstract: Sexually transmitted infections have been described as one of the major health problems in several countries of the Pacific Region. The objective of the study was to estimate the prevalence of pregnant women infected with HIV and/or syphilis in New Caledonia. HIV and syphilis test results were obtained from women attending antenatal clinics. From 2008 to 2011, 3353 pregnant women were tested with a mean prevalence of active syphilis found at 5.6/100,000. No pregnant women tested positive for HIV. Despite avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…HIV. The majority of studies up to the early 2000s found an HIV prevalence of zero to <1% among Pacific Islanders, including men and pregnant and nonpregnant women (Table 2) [6,31,32,34,[54][55][56][57][58][59][60][61]. The highest HIV prevalence was found among men and women attending an emergency department in PNG (18%) followed by FSW (10%) who had more than a 10-fold higher HIV prevalence than the general population [40,62].…”
Section: Prevalence and Incidence Data On Stis Among Pacific Islander...mentioning
confidence: 99%
See 3 more Smart Citations
“…HIV. The majority of studies up to the early 2000s found an HIV prevalence of zero to <1% among Pacific Islanders, including men and pregnant and nonpregnant women (Table 2) [6,31,32,34,[54][55][56][57][58][59][60][61]. The highest HIV prevalence was found among men and women attending an emergency department in PNG (18%) followed by FSW (10%) who had more than a 10-fold higher HIV prevalence than the general population [40,62].…”
Section: Prevalence and Incidence Data On Stis Among Pacific Islander...mentioning
confidence: 99%
“…Recent studies among other "higher-risk" populations found a syphilis prevalence of 6% in 2020 among MSM and TGW in PNG and 6% among FSW in Kiribati in 2018 [41,65]. One study from New Caledonia in 2013 reported that active syphilis was highest among people of Melanesian ethnicity [55].…”
Section: Prevalence and Incidence Data On Stis Among Pacific Islander...mentioning
confidence: 99%
See 2 more Smart Citations